Grup Media Sosial sebagai Sarana Pemberdayaan Perempuan tentang Pemberian ASI - Birgitta Bestari Puspita; Paulus A Edvra (Expose: Jurnal Ilmu Komunikasi, 2020)
Exclusive breastfeeding is still an interesting topic of discussion, especially among Indonesian women. This article is a qualitative study with interviews as data collection method. This study reveals that the group Exclusive Pumping Mama Indonesia (Eping) can serve as a place for informants in seeking breastfeeding-related information, or simply gaining more knowledge from the problems faced by other group members. By gaining such knowledge, the informants are then able to also spread such information or to educate people around them. This group has successfully established collective consciousness in breastfeeding that leads them to create real or offline actions.